Analisis Kualitas Air di Daerah Aliran Sungai Welang Rejoso pada Musim Kemarau dan Musim Hujan - Pedro Caesariano; Munawar Ali (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses topics related to water quality, fecal coliforms, total coliforms, and the comparison of the dry season and the rainy season. Apart from that, other journals discuss water quality analysis in the Welang Rejoso River Basin during the dry season and rainy season. This research aims to determine the level of river water pollution and compare it with water quality standards. The research method uses secondary data and sampling is carried out at 10 location points. The analysis results show several water parameters that exceed class III river water quality standards. It is hoped that the results of this research will help in more effective management and preservation of the river environment, with policy recommendations that need to be implemented to overcome water quality problems in the river.